2017
DOI: 10.7189/jogh.07.010417
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Clostridium difficile infections – an overview of the evidence base and challenges in data synthesis

Abstract: BackgroundRecognition of a broad spectrum of disease and development of Clostridium difficile infection (CDI) and recurrent CDI (rCDI) in populations previously considered to be at low risk has renewed attention on differences in the risk profile of patients. In the absence of primary prevention for CDI and limited treatment options, it is important to achieve a deep understanding of the multiple factors that influence the risk of developing CDI and rCDI.MethodsWe conducted a review of systematic reviews and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 60 publications
4
124
1
5
Order By: Relevance
“…After 5 days of use, its use Manuscript to be reviewed slowly increased the risk. Although previous studies revealed that antibiotic use is an important risk factor for nosocomial diarrhea (McFarland, 1995;Arevalo-Manso et al, 2014;Eze et al, 2017), this convex upward association could be a new finding. A recent study showed that the diversity of gut microbiome is affected by antibiotic administration and that the component of gut microbiome changes with time (Bulow et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…After 5 days of use, its use Manuscript to be reviewed slowly increased the risk. Although previous studies revealed that antibiotic use is an important risk factor for nosocomial diarrhea (McFarland, 1995;Arevalo-Manso et al, 2014;Eze et al, 2017), this convex upward association could be a new finding. A recent study showed that the diversity of gut microbiome is affected by antibiotic administration and that the component of gut microbiome changes with time (Bulow et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…The following variables were considered as risk factors or confounding factors for nosocomial diarrhea and were included in the analysis: age, sex, severity of illness, and number of days of use of tube feeding, PPI, H2RA, and antibiotics (McFarland, 1995;Kyne et al, 2002b;Thorson, Bliss & Savik, 2008;Arevalo-Manso et al, 2014;Eze et al, 2017;Thabit, Varugehese & Levine, 2019). The modified Rankin Scale (mRS) (van Swieten et al, 1988) was used as the index of disease severity and was scored 2 days after admission.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have provided valuable insights into the role of different risk factors for recurrent CDI [17]. However, to our knowledge, we are the first to provide insight into the risk factors for development of recurrent CDI during an outbreak.…”
Section: Discussionmentioning
confidence: 91%
“…A clinically relevant risk factor for CDAD is recent antibiotic treatment (12). There is substantial evidence supporting a causal link between microbiome disruption by antibiotics and CDAD (reviewed in (13)); however, the antibiotic effect on the microbiome seems unlikely to be the sole causal mechanism for CDAD.…”
Section: Introductionmentioning
confidence: 99%